Pengaruh Kompensasi Dan Kepuasan Kerja Terhadap Komitmen Organisasi pada PT. Bali Marine Walk - Mas Utami Dewi, Anak Agung; Dewi Adnyani, I Gusti Ayu (E-Jurnal Manajemen; Vol 3 No 11 (2014), 2014)
Human resource it is true of vital importance to fluency of aktifitas exist in in company. In the year 2012 there are 17 secretory employees and 6 employees which enter at various existing position . Problem of this research is what is there influence of signifikan by simultan and parsial of compensation and satisfaction of job to organizational komitmen in PT. Bali of Marine Walk 2) Variable which having an effect on dominant to organizational komitmen in PT. Bali of Marine Walk?. Technique analyse data use analysis of regresi doubled linear, test of F and test t. Result of test of F, assess Fhtiung bigger than value of Ftabel hence can be concluded that, compensation and satisfaction of  job by simultan have an effect on signifikan to organizational komitmen at PT. Bali of Marine Walk. Result of test of t to compensation variable (X1) show value of thitung bigger than ttabel hence can be concluded that, compensation by parsial have an effect on signifikan to organizational komitmen at PT. Bali of Marine Walk. Result of test of t to variable satisfaction of job  (X2) show value of thitung bigger than ttabel hence can be concluded that, satisfaction of job by parsial have an effect on signifikan to organizational komitmen. Variable satisfaction of job having an effect on dominant to organizational komitmen because owning value of standardized beta coefficients.
Keywords: compensation, satisfaction of job, komitmen organizational